2022
DOI: 10.3390/jfb13020047
|View full text |Cite
|
Sign up to set email alerts
|

3D Printing of Calcium Phosphate/Calcium Sulfate with Alginate/Cellulose-Based Scaffolds for Bone Regeneration: Multilayer Fabrication and Characterization

Abstract: Congenital abnormalities, trauma, and disease result in significant demands for bone replacement in the craniofacial region and across the body. Tetra-compositions of organic and inorganic scaffolds could provide advantages for bone regeneration. This research aimed to fabricate and characterize amorphous calcium phosphate (ACP)/calcium sulfate hemihydrate (CSH) with alginate/cellulose composite scaffolds using 3D printing. Alginate/cellulose gels were incorporated with 0%, 13%, 15%, 18%, 20%, and 23% ACP/CSH … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 19 publications
(11 citation statements)
references
References 65 publications
(82 reference statements)
0
11
0
Order By: Relevance
“…In this study, the 18% ACP/CSH showed the highest ALP and OCN, but the mineralization in the 20% ACP/CSH group was noticeably higher than the 18% ACP/CSH group on day 14 because sulfate ions were rapidly released on day 1 and accumulated more in ECM until day 7, which may subsequently interact with bodily fluids and affect bone mineralization [ 34 ]. However, the mechanical properties of 23%ACP/CSH were less than 20%ACP/CSH, indicating that the scaffold with lower mechanical properties provides less cell differentiation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the 18% ACP/CSH showed the highest ALP and OCN, but the mineralization in the 20% ACP/CSH group was noticeably higher than the 18% ACP/CSH group on day 14 because sulfate ions were rapidly released on day 1 and accumulated more in ECM until day 7, which may subsequently interact with bodily fluids and affect bone mineralization [ 34 ]. However, the mechanical properties of 23%ACP/CSH were less than 20%ACP/CSH, indicating that the scaffold with lower mechanical properties provides less cell differentiation [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…A 0%ACP/CSH group served as the control. To achieve a homogeneous and desirable particle size, the printing ink dispersion was filtered through a 110 μm filter [ 22 ].…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…24 Recent evidence suggests that CSC/CPC-based composite cement has favorable cytocompatibility for osteoblasts. 25–28 Further, CSC/CPC cement demonstrate the ability to induce bone regeneration in vivo . 29,30…”
Section: Introductionmentioning
confidence: 99%
“…24 Recent evidence suggests that CSC/CPCbased composite cement has favorable cytocompatibility for osteoblasts. [25][26][27][28] Further, CSC/CPC cement demonstrate the ability to induce bone regeneration in vivo. 29,30 Presently, the most common strategy to overcome the inherent limitations of inorganic cement involves the incorporation of polymer additives into the cement.…”
Section: Introductionmentioning
confidence: 99%